2018
DOI: 10.1177/0300060518786912
|View full text |Cite
|
Sign up to set email alerts
|

Medial versus lateral approach to harvesting of anterolateral thigh flap

Abstract: ObjectiveThis study was performed to evaluate two classic procedures guided by anatomic markers for harvesting the anterolateral thigh (ALT) flap: one began with an incision on the lateral side to identify perforators emerging from the muscle to the superficial tissue and to track the perforators upward to the upper stem vessel, and the other began with an incision on the medial side to identify the vessel branch from the stem artery and to track it downward to the flap perforators.MethodsTwenty-eight consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…In 2008, Adler et al 32 published a different medial incision starting technique for harvesting complex lateral femoral circumflex chimeric free tissue transfers. However, a study concluded that medial incision is more efficient than starting with a lateral incision 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, Adler et al 32 published a different medial incision starting technique for harvesting complex lateral femoral circumflex chimeric free tissue transfers. However, a study concluded that medial incision is more efficient than starting with a lateral incision 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The classic harvesting technique for the ALT flap is based on anatomic markers. It involves an open surgical procedure in which perforators are identified intra-operatively without a prior systematic investigation 33 . Thinning of the flap was initially described by Kimura et al 34 after a clear understanding of the perforasome concepts 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the operative time in this study was 138.1 (120–175) min, which was significantly shorter than the time required for free anterolateral thigh flap grafting (usually > 3 h) [ 14 , 15 ]. In thoracodorsal artery polyfoliate perforator flaps, perforators travel superficially in the intermuscular space and are easier to separate than those in the anterolateral thigh flap.…”
Section: Discussionmentioning
confidence: 99%
“…The ALT flap is mainly harvested as fasciocutaneous free flap incorporating fascia lata (FL), overlying adipose tissue and skin, or as myocutaneous flap with additional muscular component to increase bulk [5][6][7]. The FL as fascial component of the ALT flap is preferred particularly for tendon reconstruction of lower and upper limbs [8,9]. In addition, the FL is routinely used as non-vascularized graft in anterior skull base surgery or rhinology to cover small skull base defects.…”
Section: Introductionmentioning
confidence: 99%